(untitled) (Analele Universității București.Geografie, 2025)
This article aims to promote the oenological potential of the Southern Dobrogea region, as well as how it can be improved. The Southern Dobrogea Plateau has an important international wine potential, due to the natural conditions (relief, soil, climate) especially in Murfatlar and Ostrov. There, the vineyards produce an impressive range of varieties for semi-dry, dry and liqueur wines. In order to establish these wine roads, several aspects were taken into account, among which are the accessibility of the tourists to the local heritage, the current infrastructure of the territory, as well as the possibility to organize and practice tourist activities in Southern Dobrogea. Thus, the Wine Road strategy can be considered a tourist attraction in itself, but also a development strategy through which one can capitalize on the natural, anthropic, cultural and monastic tourist heritage available to Southern Dobrogea.